Distribution Evaluation Problem Based on Data Envelopment Analysis - Arabzad, S. Mohammad; Ghorbani, Mazaher; Bahrami, Mahdi (International Journal of Supply Chain Management, 2012)
Companies have found that the optimal Supply Chain Management (SCM) increases successfulness by acquiring direct and indirect benefits in the supply chain. Therefore, SCM has attracted managers and researchers attention nowadays. Distributors, as a part of a supply chain and a link between the producer and the customers, can help producers to develop new products and processes. In this paper, an integrated Kano-DEA method has introduced for distribution evaluation. This combination has used to determine the importance weights of evaluation criteria. Then, distributors have been evaluated using Data Envelopment Analysis (DEA) technique. Finally, in order to show the application aspects, a numerical example is presented.